QUALITY SERVICES AND DIGITAL ADAPTATION PT. PROLAB MEDIKA TOWARDS DIGITAL HEALTHPRENEUR: KUALITAS JASA DAN ADAPTASI DIGITAL PT. PROLAB MEDIKA MENUJU DIGITAL HEALTHPRENEUR - Hadi Kurniawanto; Inda Rohmat (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
The quality of services is crucial for companies engaged in the field of services. Its existence is expected primarily related to the difference between expectations and perceptions to see the gap that occurs in the company. As a result of the percentage, it can be seen the magnitude is above or below 50%. This is the result that can be used as a recommendation and drafting a decision. Pt. Prolab Medika engaged in clinical laboratory services such as Medical Check-Up (MCU) examination. This study aims to look at the quality of services by looking at the gap between consumers' expectations and perceptions—research methods through questionnaires and observations in the field. The study results mentioned the quality of services by 75%; it can be used to make more improvements, one of which is with recommendations for adaptation to digital. Digital adaptation is made through google business, WA business, social media, Youtube, email, to endorse celebrities.